Whatsapp e a produção de notícias: revisitando o agendamento no jornalismo contemporâneo - Feitosa, Hérica Rocha Borges (2023)
The dissertation is a study on the use of the WhatsApp messaging application within the news gathering routine and in the construction of guidelines for the television news Balanço Geral. In order to understand the use of the application in the work of the production team, participant observation was used in the team's work environment, during the period from October 03 to 14, 2022, semi-structured interview and quantitative survey of the guidelines produced in October of the same year. We also present a review of the Agenda-Setting Theory, encompassing its concepts and the functioning of the scheduling process in contemporary times. With this, it was evident that the use of the application is fundamental for the production of the television news, since the tool brought the production closer to the community, bringing new conditions and ways of verifying information, with the help of the viewers in the indication of the agendas and in the sending the information.